The association between adult attained height and sitting height with mortality in the European Prospective Investigation into Cancer and Nutrition (EPIC). - Norie Sawada; Petra A Wark; Melissa A Merritt; Shoichiro Tsugane; Heather A Ward; Sabina Rinaldi; Elisabete Weiderpass; Laureen Dartois; Mathilde His; Marie-Christine Boutron-Ruault; Renée Turzanski-Fortner; Rudolf Kaaks; et al. (PLoS ONE)
Adult height and sitting height may reflect genetic and environmental factors, including early life nutrition, physical and social environments. Previous studies have reported divergent associations for height and chronic disease mortality, with positive associations observed for cancer mortality but inverse associations for circulatory disease mortality. Sitting height might be more strongly associated with insulin resistance; however, data on sitting height and mortality is sparse. Using the European Prospective Investigation into Cancer and Nutrition study, a prospective cohort of 409,748 individuals, we examined adult height and sitting height in relation to all-cause and cause-specific mortality. Height was measured in the majority of participants; sitting height was measured in ~253,000 participants. During an average of 12.5 years of follow-up, 29,810 deaths (11,931 from cancer and 7,346 from circulatory disease) were identified. Hazard ratios (HR) with 95% confidence intervals (CI) for death were calculated using multivariable Cox regression within quintiles of height. Height was positively associated with cancer mortality (men: HRQ5 vs. Q1 = 1.11, 95%CI = 1.00-1.24; women: HRQ5 vs. Q1 = 1.17, 95%CI = 1.07-1.28). In contrast, height was inversely associated with circulatory disease mortality (men: HRQ5 vs. Q1 = 0.63, 95%CI = 0.56-0.71; women: HRQ5 vs. Q1 = 0.81, 95%CI = 0.70-0.93). Although sitting height was not associated with cancer mortality, it was inversely associated with circulatory disease (men: HRQ5 vs. Q1 = 0.64, 95%CI = 0.55-0.75; women: HRQ5 vs. Q1 = 0.60, 95%CI = 0.49-0.74) and respiratory disease mortality (men: HRQ5 vs. Q1 = 0.45, 95%CI = 0.28-0.71; women: HRQ5 vs. Q1 = 0.60, 95%CI = 0.40-0.89). We observed opposing effects of height on cancer and circulatory disease mortality. Sitting height was inversely associated with circulatory disease and respiratory disease mortality.